Absence of extended atmospheres in low-mass star radius-gap planets. Issue 1 (6th February 2023) - Krishnamurthy, Vigneshwaran; Hirano, Teruyuki; Gaidos, Eric; Sato, Bunei; Kopparapu, Ravi; Barclay, Thomas; Garcia-Sage, Katherine; Harakawa, Hiroki; Hodapp, Klaus; Jacobson, Shane; Konishi, Mihoko; Kotani, Takayuki; et al.
ABSTRACT: Kepler showed a paucity of planets with radii of 1.5–2 R⊕ around solar mass stars but this radius-gap has not been well studied for low-mass star planets. Energy-driven escape models like photoevaporation and core-powered mass-loss predict opposing transition regimes between rocky and non-rocky planets when compared to models depicting planets forming in gas-poor environments. Here, we present transit observations of three super-Earth sized planets in the radius-gap around low-mass stars using high-dispersion InfraRed Doppler spectrograph on the Subaru 8.2 m telescope. The planets GJ 9827 b and d orbit around a K6V star and TOI-1235 b orbits a M0.5 star. We limit any planet-related absorption in the 1083.3 nm lines of triplet He i by placing an upper-limit on the equivalent width of 14.71, 18.39, and 1.44 mÅ for GJ 9827 b (99 per cent confidence), GJ 9827 d (99 per cent confidence), and TOI-1235 b (95 per cent confidence), respectively. Using a Parker wind model, we cap the mass-loss at >0.25 M⊕ Gyr −1 and >0.2 M⊕ Gyr −1 for GJ 9827 b and d, respectively (99 per cent confidence), and >0.05 M⊕ Gyr −1 for TOI-1235 b (95 per cent confidence) for a representative wind temperature of 5000 K. Our observed results for the three planets are more consistent with the predictions from photoevaporation and/or core-powered mass-loss models than the gas-poor formation models. However, more planets in the radius-gap regime around the low-mass stars are needed to robustly predict the atmospheric evolution in planets around low-mass stars.